RANCANGAN BANGUN SISTEM PEMANTAUAN pH AIR - Rizky Adi Sanjaya; Raden Arief Setyawan; n/a Rahmadwati (Jurnal Mahasiswa TEUB, 2022)
Water quality is known by conducting certain tests on water quality standards. The purpose of this study is to determine the physical characteristics of water quality and to produce a system that can monitor the pH of the water in order to keep the water in an ideal state. The method used is a prototype method by making a water quality detector using a pH sensor using Arduino Uno with the process of collecting needs, building a system, coding the system, testing the system, and evaluating the system. Arduino Uno as a control center will send sensor data that has been processed to the Wemos D1 mini connected to wifi. Then it will be sent to the Blynk server so that it can be displayed on the user’s smartphone and convey the resulting data notification. pH measurement obtained an averange value of 96.41% accuracy. The results of testing different water systems have different pH. Test results notification delay time average delay time pH 4.5 seconds. The existence of blackbox testing – testing has a level of suitability of the application to the user by 100%. The language of the notification can be set according to the needs, so as to adjust the area where the device will be installe